1984
DOI: 10.1111/j.1365-2265.1984.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Gabaergic Drug, Sodium Valproate, on the Prolactin Release Evoked by Pharmacological Stimuli in Normal Women

Abstract: Sodium valproate (DPA or Na-dipropylacetate), an anticonvulsant drug activating the endogenous GABAergic system, was administered orally at the dose of 400 mg to seventeen normal women 1 h before intravenous injections with three drugs which stimulate prolactin (PRL) release: TRH (200 micrograms bolus; six subjects); domperidone (5 mg bolus; six subjects); and sulpiride (5 mg bolus; five subjects). DPA pretreatment significantly blunted PRL response to both domperidone and sulpiride injections without affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Early studies in normal (short-term VPA use) and epileptic (long-term VPA use) populations did not indicate an effect of VPA on prolactin [150,[167][168][169]. In 1988, Bilo et al found increased concentrations of prolactin in a female epileptic population but could not definitively relate it to AED use, or VPA use in particular [139].…”
Section: Prolactinmentioning
confidence: 92%
“…Early studies in normal (short-term VPA use) and epileptic (long-term VPA use) populations did not indicate an effect of VPA on prolactin [150,[167][168][169]. In 1988, Bilo et al found increased concentrations of prolactin in a female epileptic population but could not definitively relate it to AED use, or VPA use in particular [139].…”
Section: Prolactinmentioning
confidence: 92%
“…Similarly, in our patients (receiving PB and/or VPA), the elevation of mean basal PRL does not seem related to an AED effect. In fact, previous studies in normal women have never shown increased PRL levels after PB administration (Rosadini et al, 1983;Luoma et al, 1984), and VPA has been reported to blunt PRL levels in women (Melis et al, 1982(Melis et al, , 1984Giroud et al, 1985;Minervini et al, 1987).…”
Section: Time ( M I Dmentioning
confidence: 93%
“…The loss of inhibitory effect does not appear to be dependent on the presence of hyperprolactinaemia [12,13], In treated pro lactinoma patients with normalized serum prolactin lev els, there is still a failure of sodium valproate to inhibit prolactin release [T.H. Jones, unpubl.…”
Section: Introductionmentioning
confidence: 99%